Pengaruh Celebrity Endorser dan Brand Image Terhadap Keputusan Pembelian Sabun Mandi Lux Pada Mahasiswa S-1 FISIP UNDIP Semarang - Faridlotul Chusnah; Sudharto Prawata Hadi; Sri Suryoko (Universitas Diponegoro, 2015)
The development of information technology can lead consumers to quickly find out information about the existence of a product. Companies are required to provide information about their products correctly so it gets a positive response from consumers. Marketing strategies do companies is to provide information to consumers through advertising. By using celebrity endorsers in advertising is expected to attract the attention of consumers and increase and can form brand image. The main problem in this research is about target that is never reached in 2011-2013 that is not optimal. This research aims to identify that the influence of celebrity endorser and the brand image of the decision the purchase of bath soap Lux.This study aims to determine the influence of service quality. Whith survey approach, which requires sample of population and questioner as a means of data collection. This research is conducted to 100 responders which buy “Lux” soap. Technique of sample is purposive sampling. The analysis method used is a correlation coefficient, the coefficients determined, linear regression simple, linear regression double, T test and F test with program SPSS version 20.Based on the result analysis, celebrity endorser and brand image are able to explain the variables of buying decision. Kontribution celebrity endorser of the buying decision as 36,4% and kontribution brand image of the buying decision as 18,5%. Celebrity endorser have value dominant as 0,528.The conclusion of this research indicated that celebrity endorserand brand image partially and simultaneously has an influence on the making decision “Lux” soap. Based on the result, PT. Unilever Indonesia, Tbk has to choose credible celebrity, maintan and improve the brand image of the company. Advice for PT. Unilever Indonesia, Tbk is retaining a celebrity who has the credibility of good and doing innovation to improve the brand image of a bath soap Lux.